Comparison of Prevalence and Risk Factors of PTSS Between Chinese Patients With Depression and Non-depressed Controls During COVID-19 Outbreak - Peng, Min; Song, Xinran; Liu, Luyu; Zhao, Weifeng; Lai, Pingmei; Bao, Guanglin; Guo, Tianyou; Zhang, Xiangyang (Frontiers in Psychiatry, 2022)
Background: COVID-19 pandemic is a traumatic event all over the world, and may lead to post-traumatic stress symptom (PTSS) in different population who are under the threat of novel corona virus. Therefore, our study aim to compare the prevalence and risk factors of PTSS between Chinese patients with depression and non-depressed controls during the COVID-19. Methods: 437 depressed patients and 2940 non-depressed controls were enrolled in this cross-sectional study between February 14 and May 9, 2020. The Impact of Events Scale-Revised (IES-R), Zung Self-Rating Depression Scale (SDS), Zung Self-Rating Anxiety Scale (SAS) and Pittsburgh Sleep Quality Index (PSQI) were used to evaluate the psychological status. Results: The prevalence of PTSS (IES-R ≥ 33) in depressed patients (45.08%) was higher than that in non-depressed controls (5.31%). Patients with depression were 16 times more likely to suffer from PTSS than those without depression. Correlation analyses showed that the IES-R total score was positively correlated with SDS, SAS, and PSQI scores in both depressed and non-depressed groups (Bonferroni corrected all p＜0.001). Multiple regression analysis showed that SAS and PSQI scores were independently associated with IES-R total score in both depression and non-depression groups. In patients with depression, education level and time of media exposure to COVID-19 were positively associated with PTSS, while in the non-depressed group, subjects who were married, in 31–50 years old age group, or had higher SDS score were more prone to PTSS. Limitations: This study used a cross-sectional design. Conclusions: These results indicate that the prevalence of PTSS in patients with depression is very higher than that in subjects without depression. PTSS are associated with a number of socio-demographic and clinical variables.